Factors associated with the development of hypertension among surgical menopause women at Hospital Universiti Sains Malaysia - Dahian, Ahaddiah (2018)
Introduction: Surgical menopause defined as attained menopause after surgically removal of uterus with bilateral oopherectomy or removal of both ovaries only. Surgical menopause increases the risk of development of hypertension which is predisposed to the development of the cardiovascular complications.Objective: To determined factors associated with the development of hypertension among postsurgical menopausal women.